Salbutamol Versus Nifedipine Dans Le Traitement De La Menace D’accouchement Premature A La Maternite Du Centre Hospitalier Universitaire Et Departemental Du Borgou - Ahouingnan, N.F.M. Hounkponou; Bagnan, A. Tonato; RI, Sidi; M., Vodouhe; AAA, Obossou; H., Laourou; Tankoua, P.P. Ntankeu; K., Salifou (European Scientific Journal, ESJ, 2017)
Introduction: The threat of the premature birth (TPB) raises a problem of public health in Benin in general and in Parakou in particular. Objective: The aim of this research paper is to compare the efficiency of salbutamol and nifedipine in the treatment of the threat of premature birth at the maternity hospital of CHUD-Borgou. Framework and methodological approach: It is about a comparative prospective study with analytical view, within a period of six (06) months, going from 1, March 2016 to 1, September 2016. The target population is composed of all the pregnant women admitted to the maternity hospital of CHUD-B during the period of the study. Results: The 60 pregnant women have been divided into two groups of 30 pregnant women. The average age of the pregnant women is 26.50 years with the extremes of 16 years and 38 years. The women who have between two and three pregnancies are the most represented with 56.67% of the cases; just as much as the women who have between two and three deliveries with 36.67%. From the total number, 21. 67% had antecedents of spontaneous miscarriages and 6, 67% antecedents of premature birth delivery. With 90% of the cases, the gestational age is between 28 weeks of amenorrhoea and 33weeks of amenorrhoea plus six (06) days. The pregnancy is twin in 16.67% of the cases. At the admission, 90% of the cases after assessment of the Coefficient of Risk of Premature birth Delivery. (CRPD), had a potential risk of prematurity and 85% had a score of Baumgarten between 3 and 6. The most discovered aetiology is malaria with 46.67% of the pregnant women. The side effect of usage of nifedipine, in order to relieve the uterus, has been noticed with 16.67% pregnant women who have received nifedipine treatment against 30% pregnant women who have received the treatment of Salbutamol. There is no difference statistically significant. For the nifedipine, there is 90% of success against 10% of failure. For salbutamol, there is respectively 56.67% and 43.33%. We have no case of intolerance. Conclusion: The study shows neat efficiency of nifedipine in relation to salbutamol during the treatment of the threats of premature birth delivery.